Determinant Factors Associated with Behavior of COVID-19 Vaccination Acceptance in Elderly in Manutapen Health Center, Kupang, East Nusa Tenggara - Pius Weraman; Ferderika Lobo (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: COVID-19 disease is a disease caused by a person novel corona virus. one Vaccination is an effort made by the government for forming herd immunity and protected or immune to certain diseases, causing an indirect impact, namely being protected. vulnerable community groupsThis study aims to analyze the determinants of factors that influence the behavior of the elderly towards the acceptance of COVID-19 vaccination at the Manutapen Health Center, Kupang.Subjects and Method: This observational analytic study was conducted at Manutapen Health Center, Kupang, East Nusa Tenggara. A total of 88 subjects was selected by simple random sampling. The dependent variables were behavior of the elderly towards receiving the COVID-19 vaccination. The independent variables are education, knowledge, attitudes, personal experience, social support, availability of information. The data wer collected using questionnaire and analyzed using Chi Square test and logistic regression.Results: The behavior of the elderly towards receiving the COVID-19 vaccination, including the level of education (OR= 5.83; 95 % CI= 1.52 to 22.29; p= 0.001), knowledge (OR= 2.21; 95 % CI= 1.30 to 3.75; p= 0.001), attitude (OR= 2.61; 95 % CI= 1.51 to 4.51; p= 0.001), and information availability (OR= 2.42; 95 % CI= 1.43 to 4.11; p= 0.001).Conclusion: Factors associated with elderly towards receiving the COVID-19 vaccination, including the level of education, knowledge, attitude, and information availability.Keywords: determinant factors, behavior of the elderly, covid-19 vaccination.Correspondence:Pius Weraman. Masters Program in Public Health, Faculty of Public Health, Universitas Nusa Cendana. Jl. Adi Sucipto Penfui, Penfui, Maulafa, Kupang, Nusa Tenggara Timur. Email: piusweraman@yahoo.com. Mobile: +62812-3789-293.Journal of Health Promotion and Behavior (2022), 07(03): 262-272DOI: https://doi.org/10.26911/thejhpb.2022.07.03.08